Citrus black spot is absent in the Western Cape, Northern Cape and Free State Provinces - Elma Carstens; Hendrik le Roux; Michael Holtzhausen; Liezl van Rooyen; Joey Coetzee; Ria Wentzel; Wilhelm Laubscher; Zorina Dawood; Elrita Venter; Gerhardus Schutte; Paul Fourie; Vaughan Hattingh (South African Journal of Science)
The South African citrus industry is strongly focused on exports and South Africa is a signatory member of both the World Trade Organisation Agreement on the application of Sanitary and Phytosanitary Measures and the International Plant Protection Convention. Citrus black spot, caused by Guignardia citricarpa, does not occur in all the South African citrus production areas and, therefore, South Africa has a responsibility to provide those trading partners that have identified G. citricarpa as a regulated pest with reliable information about the distribution of citrus black spot within South Africa. Detection surveys were conducted in citrus production areas in the Western Cape, Northern Cape and Free State Provinces and appropriate diagnostic protocols were used to ensure reliable detection of G. citricarpa. Trees in commercial orchards and home gardens on farms and in towns of 17, 9 and 5 magisterial districts in the Western Cape, Northern Cape and Free State Provinces, respectively, were sampled between 1995 and 2010. Fruit samples were taken during June and July, and leaf samples from November to January. None of the 3060 fruit and leaf samples collected during these surveys tested positive for G. citricarpa. Phyllosticta capitalensis, a non-pathogenic, ubiquitous, endophytic species was, however, detected during these surveys. In compliance with relevant International Standards for Phytosanitary Measures and based on the outcome of these official surveys, these three provinces in South Africa can be recognised as citrus black spot pest free areas.